SOSIALISASI FISIOTERAPI TENTANG DETEKSI DINI AUTISME DI POSYANDU SIDOMULYO DESA KEDUNGMULYO BOYOLALI JAWA TENGAH - Muhammad Iqbal Yazid Fazry; Arin Supriyadi (Universitas Majalengka, 2022)
Kedungmulyo Village is a village located in the district of Need, Purworejo, Central Java, Indonesia. Kedungmulyo Village is one of 41 villages in Need District which has a distance of 30 km from the district city. Kedungmulyo Village has an area of ​​169,320 Ha / 0.9 Km2. The population in Kedungmulyo Village is 1619 people (359 families) consisting of 736 men and 883 women spread over four hamlets. Various kinds of diseases can be experienced by a person, including newborn children, therefore in order to increase public knowledge and understanding of children's development which is very important for the future, it is necessary to carry out physiotherapy socialization in recognizing and preventing a symptom. One of the diseases that can be experienced by these children is Autism.